2021
DOI: 10.1126/sciimmunol.abj3859
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation triggers gasdermin D–independent inflammation

Abstract: Sustained stimulation of the NLRP3 inflammasome causes inflammation in the absence of GSDMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 85 publications
4
104
1
Order By: Relevance
“…Indeed, the phenotype of either single mutant strain implied non-redundant functions of both GSDMs whereas the outcomes of compound mutants suggested that they shared downstream effector molecules. The latter view was supported by the ability of either GSDM to mediate pyroptosis and IL-1β and IL-18 release in cell a context-dependent manner (35,(37)(38)(39)(40). Furthermore, functional complementation of GSDMD by GSDME has also been reported (35).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Indeed, the phenotype of either single mutant strain implied non-redundant functions of both GSDMs whereas the outcomes of compound mutants suggested that they shared downstream effector molecules. The latter view was supported by the ability of either GSDM to mediate pyroptosis and IL-1β and IL-18 release in cell a context-dependent manner (35,(37)(38)(39)(40). Furthermore, functional complementation of GSDMD by GSDME has also been reported (35).…”
Section: Discussionmentioning
confidence: 98%
“…The latter view was supported by the ability of either GSDM to mediate pyroptosis and IL-1β and IL-18 release in cell a context-dependent manner (35,(37)(38)(39)(40). Furthermore, functional complementation of GSDMD by GSDME has also been reported (35). Thus, although additional studies are needed for further insights onto the mechanism of differential actions of GSDMD and GSDME in bone recovery after injury, our findings reinforce the crucial role that inflammation plays during the bone fracture healing process.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…GSDMD is also involved in the pathogenesis of complex diseases including experimental autoimmune encephalitis, radiation-induced tissue injury, ischemia/reperfusion injury, sepsis, renal fibrosis, and thrombosis ( Li et al, 2019 ; Xiao et al, 2020 ; Zhang et al, 2019 ; Silva et al, 2021 ; Zhang et al, 2021c ; Zhang et al, 2021a ). Other well-studied GSDMs include GSDMA and GSDME ( Liu et al, 2021 ; Zhang et al, 2020 ; Wang et al, 2021 ; Zhou et al, 2020 ). GSDME is of particular interest to this study because recent evidence suggests that it harbors overlapping and non-overlapping actions with GSDMD, depending on cell contexts.…”
Section: Introductionmentioning
confidence: 99%